A rare case of a solitary fibrous tumor of vulva, displaying NAB2ex6-STAT6ex17 fusion - Bharat Rekhi; Prachi Bapat; Arpita Jindal (Wolters Kluwer Medknow Publications, 2021)
A solitary fibrous tumor (SFT), although ubiquitous, is rarely documented in the female genital tract, especially confirmed by STAT6 immunostaining and underlying NAB2-STAT6 gene fusion. A 24-year-old female presented with a gradually increasing vulvar swelling in her right labia, which rapidly increased in size over 1-year duration. Radiologically, a subcutaneous, predominantly solid, lobulated mass, measuring 10 cm in the largest dimension was seen involving her right labia majora and perineum. She underwent tumor resection, elsewhere, where it was reported as a pleomorphic sarcoma. Histopathologic review revealed a cellular tumor comprising spindle cells, displaying mild nuclear variation, arranged diffusely and focally, in a hemangiopericytomatous growth pattern, within a collagenous stroma. Interspersed were blood vessels with perivascular hyalinization and few giant cells. By immunohistochemistry, tumor cells showed patchy immunostaining for CD34 and diffuse immunostaining for STAT6. Furthermore, the tumor displayed NAB2ex6-STAT6ex 17 fusion by RT-PCR technique. This case constitutes one of the few reported cases of vulvar SFT, confirmed by STAT6 immunostaining and the second such case, displaying NAB2-STAT6 gene fusion. Diagnostic and treatment implications are discussed herewith.